2020
DOI: 10.1002/anie.202005313
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric [8+2] Dipolar Cycloadditions of Vinyl Carbamates and Photogenerated Ketenes

Abstract: Higher-order cycloadditions, particularly [8+2] cycloadditions, are a straightforward and efficient strategy for constructing significant medium-sized architectures. Typically, configuration-restrained conjugated systems are utilized as 8pcomponents for higher-order concerted cycloadditions. However, for this reason, 10-membered monocyclic skeletons have never been constructed via catalytic asymmetric [8+2] cycloaddition with high peri-and stereoselectivity. Here, we accomplished an enantioselective [8+2] dipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…In 2020, Lu and coworkers developed an enantioselective [8+2] dipolar cycloadditions of 6‐vinyl‐1,3‐oxazinan‐2‐ones 99 and ketenes 48 via the merger of visible‐light activation and asymmetric palladium catalysis (Scheme 51, top) [36] . In this work, the substituent on N atom of 99 had a great influence on the periselectivity.…”
Section: π‐Allyl Palladium Bearing N‐nucleophilementioning
confidence: 97%
“…In 2020, Lu and coworkers developed an enantioselective [8+2] dipolar cycloadditions of 6‐vinyl‐1,3‐oxazinan‐2‐ones 99 and ketenes 48 via the merger of visible‐light activation and asymmetric palladium catalysis (Scheme 51, top) [36] . In this work, the substituent on N atom of 99 had a great influence on the periselectivity.…”
Section: π‐Allyl Palladium Bearing N‐nucleophilementioning
confidence: 97%
“…(43b) closed the ring and gave cyclobutyl iminium ions (43c) which could further release the desirable products (39) and finish a catalytic cycle. Bach et al found a co-catalytic system with ruthenium catalyst (Ru(bpz) 3 (PF 6 ) 2 ) and a chiral secondary amine catalyst (44) to synthesize cyclobutanecarbaldehydes (45) from α,β-unsaturated aldehydes (46) and olefins (47) upon the irradiation of visible light (λ = 458 nm) in moderate to good yields and enantioselectivity (49-74% yield, 83-96% er) (Scheme 11) [21]. A variety of substituents such as bromo, chloro, trifluoromethyl, methoxy, pinacolatoboryl, and acetoxy groups at the aryl moiety of α,β-unsaturated aldehydes are reliable substrates.…”
Section: Enantioselective Formation Of 4-membered Ring By Visible Light Catalysismentioning
confidence: 99%
“…In 2020, Xiao et al reported palladium-catalyzed asymmetric [8+2] dipolar cycloadditions. In the presence of a chiral ligand (164) and Pd 2 (dba) 3 •CHCl 3 , vinyl carbamates (165) could react with photogenerated ketenes (166) to deliver 10-membered cycloadducts (167) upon the diffraction of blue LED light in excellent yields and enantioselectivity (up to 97% yield, up to 97% ee) (Scheme 36) [46]. A variety of vinyl carbamates bearing different aryl groups could afford desired cycloadducts with high er, and unsaturated vinyl group substituted with vinyl carbamate could be well tolerated in asymmetric [8+2] cycloaddition.…”
Section: Enantioselective Formation Of Macroring By Visible Light Catalysismentioning
confidence: 99%
“…The Xiao group constructed medium-sized rings by utilizing asymmetric [8 + 2] dipolar cycloadditions with palladium catalysis in combination with chiral ligands and visible light activation. [35] In the first step, diazoketones upon illumination release N 2 forming ketenes, then the reaction mixture is transferred to the solution of Pd catalyst and ligand 24 a. Formation of enantioenriched 10-membered monocyclic compounds takes place with high periselectivity (Scheme 28).…”
Section: Studies With Palladium Preparationsmentioning
confidence: 99%